Book review: Helen Kensett, Sales Mind: 48 Tools to Help You Sell, 2016. Issue 3 (September 2022) - Mukherjee, Jaydeep
Helen Kensett, Sales Mind: 48 Tools to Help You Sell, 2016, Profile Books Ltd., 208 pp., ₹263. ISBN: 9781781256312 (Hardback).